2020
DOI: 10.1088/1755-1315/451/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Land priority area for agribusiness development based on human and economic resources in Central Java

Abstract: The agricultural sector is the main sector almost in every region in Indonesia and also in Central Java. The agricultural sector needs more land for agribusiness development. Agribusiness development referrals are away on making use of those potentials. This study aims to determine the land priority area for agriculture development based on human and economic resources in Central Java using DR (Dependency Ratio), LP (Labour Productivity), LQ (Location Quotient), Food Security, and Land Carrying Capacity (LCC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Calculation of population pressure in Jakarta Special Province using all three models showed that the value of population pressure in Jakarta Special Province was almost all above one (TP>1). This meant that the population pressure with the model I in Jakarta Special Province was so high that it is unable to meet the living needs of the population in these areas [20]. This can be caused by the increasing number of residents in Jakarta Special Province from year to year and the conversion of agricultural land to non-agricultural land.…”
Section: Population Pressurementioning
confidence: 99%
“…Calculation of population pressure in Jakarta Special Province using all three models showed that the value of population pressure in Jakarta Special Province was almost all above one (TP>1). This meant that the population pressure with the model I in Jakarta Special Province was so high that it is unable to meet the living needs of the population in these areas [20]. This can be caused by the increasing number of residents in Jakarta Special Province from year to year and the conversion of agricultural land to non-agricultural land.…”
Section: Population Pressurementioning
confidence: 99%
“…With the support of fertile land and soil, the agricultural sector in Indonesia is considered very promising. The agricultural sector in Indonesia plays an important role in improving the economic sector and meeting basic food needs (Virgawati, 2012;Putri et al, 2020). Therefore, the farming community has an important role in the structure of national economic development.…”
Section: Introductionmentioning
confidence: 99%